The Effect of a G:T Mispair on the Dynamics of DNA - Imhof, Petra; Zahran, Mai (PLoS ONE, 2013)
Distortions in the DNA sequence such as damages or mispairs are specifically recognized and processed by DNA repair enzymes. A particular challenge for the enzymatic specificity is the recognition of a wrongly-placed native nucleotide such as thymine in T:G mispairs. An important step of substrate binding which is observed in many repair proteins is the flipping of the target base out of the DNA helix into the enzyme's active site. In this work we investigate how much the intrinsic dynamics of mispaired DNA is changed compared to canonical DNA. Our molecular dynamics simulations of DNA with and without T:G mispairs show significant differences in the conformation of paired and mispaired DNA. The wobble pair T:G shows local distortions such as twist, shear and stretch which deviate from canonical B form values. Moreover, the T:G mispair is found to be kinetically less stable, exhibiting two states with respect to base opening: a closed state comparable to the canonical base pairs, and a more open state, indicating a proneness for base flip. In addition, we observe that the thymine base in a T:G mispair is significantly more probable to be flipped than thymine in a T:A pair or cytosine in a C:G pair. Such local deformations and in particular the existence of a second, more-open state can be speculated to help the target-site recognition by repair enzymes. © 2013 Imhof, Zahran.
CRIS-Team Scopus Importer:2020-02-18